Cities and clusters: Economy-wide and sector-specific effects in corporate location - Giulio Bottazzi; Ugo Gragnolati (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
Are the observed spatial distributions of firms decided mostly by market-mediated, economy-wide locational forces, or rather by non-pecuniary, sector-specific ones? This work finds that the latter kind of forces weight systematically more than the former in deciding firm location. The analysis uses Italian data on a variety of manufacturing and service sectors spatially disaggregated at the level of Local Labor Systems.
Keywords: L1; C31; R3; 330; Industrial Location; Sector-specific Agglomeration; Urbanization Economy; Maximum Likelihood Estimation; Produktionsstandort; Agglomerationseffekt; Regionales Cluster; Maximum-Likelihood-Methode; Italien